Maximization of Micropropagule Production in an Attractive Ornamental Plant, Oxalis triangularis A.st.-Hil - Klaocheed, Sutha; Rittirat, Suphat; Kalawong, Soontreeya; Thammasiri, Kanchit (Trends in Sciences, 2024)
Petiole segments of an economically ornamental plant Oxalis triangularis A.st.-Hil have been used in the present study for rapid, reliable and systematic in vitro propagation. The morphogenic effect of α-Naphthalene acetic acid (NAA) at various concentrations (0.5 - 3.0 mg/L) was studied individually or in combination with 6-benzylaminopurine (BAP). Superior multiplication rates were achieved on Murashige and Skoog (MS) medium supplemented with 0.5 mg/L NAA and 1.0 mg/L BAP. Of the tested combinations, maximum shoot regeneration (100.00 %), mean shoot number (14.60 ± 0.37 shoots per segment), and shoot length (18.11 ± 0.30 mm) were recorded on MS medium supplemented with 0.5 mg/L NAA and 1.0 mg/L BAP after 6 weeks of incubation. Half-strength MS medium augmented with 1.0 mg/L indole-3-butyric acid (IBA) was the optimal medium for in vitro root induction, (24.60 ± 0.37 roots per shoot with 9.10 ± 0.32 mm in length) after 6 weeks of incubation. The regenerated plantlets showed 100 % survival success during acclimatization and exhibited normal growth characteristics and morphology. This optimized protocol is cost-effective and highly efficient for the rapid mass propagation of Oxalis triangularis A.st.-Hil. HIGHLIGHTS The tissue culture technology was successfully employed for developing a practicable simple, efficient, and amenable protocol for mass multiplication of Oxalis triangularis A.st.-Hil, an economically ornamental plant Our studies based on interaction and combinations of auxins with BAP provided better shoot proliferation The regenerated plantlets survived well under field conditions This optimized protocol is cost-effective and highly efficient for the rapid mass propagation of Oxalis triangularis A.st.-Hil GRAPHICAL ABSTRACT